Hybrid artificial intelligent systems : 10th International Conference, HAIS 2015, Bilbao, Spain, June 22-24, 2015, Proceedings /: 10th International Conference, HAIS 2015, Bilbao, Spain, June 22-24, 2015, Proceedings. (2015) - Unknown
No abstract available